Here's the question you clicked on:
Calabunga
Solve the system using elimination. system (1 point) (2, 1) (0, –2) (–2, 0) (1, 2)
2x + 6y = -12 ---> (-5)2x + 6y = - 12 5x - 5y = 10 ----> (2)5x - 5y = 10 -------------------------------- -10x - 30y = 60 (result of multiplying by -5) 10x - 10y = 20 (result of multiplying by 2) --------------------------------- -40y = 80 -40y/-40 = 80/-40(divide both sides by -40) y = - 2 now sub - 2 in for y in either of the original equations... 5x - 5y = 10 5x -5(-2) = 10 5x + 10 = 10 5x = 10 - 10 5x = 0 5x/5 = 0/5 x = 0 check... 2x + 6y = -12 2(0) + 6(-2) = -12 0 - 12 = -12 -12 = -12 (correct) answer : (0, -2)
your quite welcome :)